Case Report: Systemic Sclerosis After Covid-19 Infection - Fineschi, Serena (Frontiers in Immunology, 2021)
The coronavirus disease (COVID-19) is a respiratory tract infection caused by the new virus SARS-CoV-2. The acute phase of the infection may in certain individuals be followed by another longer phase of disease (long COVID) of unknown etiology probably associated in certain cases with autoimmune activation. It has been shown that COVID-19 can trigger autoantibody production and in genetically predisposed patients may cause the onset or exacerbation of autoimmune diseases. We are reporting a case of mild COVID-19 infection complicated by autoantibody production and cutaneous and gastrointestinal symptoms and subsequently diagnosed with systemic sclerosis (SSc). A 47-year-old man with no history of any autoimmune diseases and in good health became sick together with his family on the 12th of November with mild symptoms: tiredness, fever, cough, and sore throat. Oropharyngeal swab for SARS-CoV-2 tested positive. He was isolated at home and did not require hospitalization. Three weeks later he presented with clinical manifestation compatible with suspicion of SSc. He briefly presented with skin rush, periorbital edema and conjunctivitis, vomiting, dysphagia, burning sensation in the skin, above all in the fingertips and around the mouth, puffy fingers, Raynaud’s phenomenon, pain at the fingertip of the middle finger where a depressed area was noticed without a clear ulceration. ANA showed a strongly positive nucleolar pattern. Anti-PM/Scl 75 and PM/Scl 100 resulted positive. High-resolution computed tomography (HCRT) showed early stage of interstitial lung disease (ILD). The patient was diagnosed with SSc based on the persistence of autoantibodies and the clinical and radiological pictures according to the ACR/EULAR classification (scores: puffy finger, 2; ILD, 2; Raynaud’s phenomenon, 3; SSc related antibodies, 3; total 10). There are several cases described in the medical literature of possible new onset of SLE after COVID-19 infection. This is the first case that describes a possible new onset of SSc. Conclusion: SARS-CoV-2 may trigger systemic sclerosis.